The brand-new predictor index of fulminant process in patients with acute myocarditis: hemoglobin, albumin, lymphocyte and platelet (HALP) score - Aladag, Pelin; Avci, Ahmet (Frontiers in Nutrition, 2025)
Background/objectivesMyocarditis can progress to a fulminant form, leading to severe heart failure and mortality. Inflammation and nutritional status play critical roles in disease progression. The hemoglobin, albumin, lymphocyte, and platelet (HALP) score is a novel, easily accessible biomarker that reflects both systemic inflammation and nutritional status. This study aimed to evaluate the prognostic value of the HALP score in predicting fulminant myocarditis among patients diagnosed with acute myocarditis.MethodsA total of 124 patients diagnosed with acute myocarditis were retrospectively enrolled in this single-center study. Patients were categorized into non-fulminant and fulminant myocarditis groups based on diagnostic criteria.ResultsThe median age of the patients was 24 years, 14.5% was female. Twenty-three of these patients (18.5%) exhibited fulminant myocarditis. Troponin I, C-reactive protein (CRP), white blood cell (WBC), and N-terminal pro-brain natriuretic peptide (NT-proBNP) levels were significantly higher in the fulminant myocarditis group, while the HALP score was lower (p < 0.001 for all). Multivariable regression analysis identified WBC, NT-proBNP and HALP score as independent predictors of fulminant myocarditis (p = 0.029, p = 0.011 and p = 0.046, respectively). The optimal cut-off value of the HALP score was 4.12 for predicting fulminant myocarditis, with an area under the curve of 0.814. Beyond its diagnostic utility, a low HALP score was also significantly associated with worse clinical outcomes.ConclusionThe HALP score can independently predict the development of fulminant myocarditis in acute myocarditis patients.